Game-changing Partnerships for Game-changing Solutions for Food and Climate - Korngold, Alice (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
ENSURE ACCESS TO SAFE AND NUTRITIOUS FOOD FOR ALL • Addressing food loss and waste in supply chains, food security, and greenhouse gas emissions. Multi-stakeholder research and development. Leveraging technology to coordinate food distribution. • Innovating to advance the SDGs. 2. SHIFT TO SUSTAINABLE CONSUMPTION PATTERNS • Transforming diets to address pressing issues of malnutrition and obesity, while also reducing greenhouse gas emissions. Public policies to promote healthier foods. Access to affordable, nutritious food. Market incentives for farmers to advance sustainable agriculture. • Engaging 10 million young people in science-based social movements to catalyze climate action in food systems. 3. BOOST NATURE-POSITIVE PRODUCTION • Addressing the adverse impacts of agricultural production on critical ecosystems including tropical forests, peatlands, savannas, and grasslands. • Empowering 200 million farmers through the development of markets and implementing climate-smart agricultural practices to support resilience and protability. • Unlocking USD 320 billion per year from both public and private nance to create business opportunities for sustainable nance. 4. ADVANCE EQUITABLE LIVELIHOODS • Closing the gender gap in agriculture and food systems that make it dicult for women to have access to resources and opportunities, including capital, technology, and land tenure. 5. BUILD RESILIENCE TO VULNERABILITIES • Empowering 200 million farmers through the development of markets and implementation of climate-smart practices for resilience and protability.